The role of psychological rehabilitation programs in community reintegration of people of determination: Field study - Zayed Higher Organization in Abu Dhabi as a model - Al Shehhi, Alia; Alhourani, Mohammed (Al-Adab Journal, 2024)
The study aimed to reveal the role of psychological rehabilitation programs in the societal reintegration of people of determination, and to address the growing impact they have on the reintegration of people of determination, and the impact of this on the psychological state of people of determination, and the increasing levels of their integration into society. An applied study was conducted at the Zayed Higher Organization for People of Determination in Abu Dhabi, and the opinions of the beneficiaries were surveyed about the institution’s psychological rehabilitation programs, using the social survey approach through personal interviews with (70) beneficiaries. The interviews resulted in a number of results that were summarized in that the rehabilitation programs... Psychological services play a major role in improving the levels of community participation for people of determination and contribute significantly to their reintegration. These programs also have a growing role in improving the levels of community integration of people of determination through designing and planning a number of effective programs in implementing that role. Psychological rehabilitation is considered one of the necessities of community rehabilitation for people of determination to reintegrate them into society, and psychological rehabilitation programs are programs with special and specific standards and capabilities that are commensurate with the capabilities of people of determination, but they have common denominators that aim to integrate people of determination into society, control their behaviors, and enable them to Building social relationships. The study recommended the necessity of practicing and implementing psychological rehabilitation programs on a continuous and organized basis for people of determination, especially since they have proven their effectiveness in integration. It also recommended the necessity of adopting a transparent methodology and a clear vision regarding care centers for people of determination and supporting them logistically and financially to ensure higher achievement. Quality level rates for serving people of determination.